Acoustic studies of molecular interactions of chlorhexidine with glycols at different temperatures. Issue 1 (1st May 2022) - Kaur, Parminder; Juglan, K.C.; Kumar, Harsh
Abstract: The Density and Ultrasonic Velocity of chlorhexidine with glycols have been measured at different range of temperatures for different concentrations. Ultrasonic and volumetric data has been used to calculate various parameters such as adiabatic compressibility, acoustic impedance, available volume, molar volume, intermolecular free length, Rao's constant, Van Der Waal Constant, Wada's constant, relative intensity, and effective molecular weight. The calculated various parameters suggest solute-solvent interactions occurring in the liquid mixtures. Some other parameters suggest dipole-dipole interactions or formation of complex or charge transfer interactions.